It's No Illusion, You Can Pay Taxes with a Smile : The Rwanda Case - Murangwa, Hadija; Mukunya, David (International Finance Corporation, Washington, DC, 2015)
In the push for tax reform, there was a twofold guiding principle: 1) to lower the cost of compliance for taxpayers, reduce the cash flow burden by allowing quarterly rather than monthly tax payments and expediting refunds, and minimize points and frequency of contact between taxpayers and the tax authority; and 2) to safeguard government revenue by protecting collections and reducing administrative costs. The ultimate objective was to encourage businesses to pay taxes via a more attractive system. Since 2008, the government of Rwanda has emphasized Doing Business reforms to improve Rwanda s attractiveness to local and international investors. In response, the World Bank Group launched its investment climate reform project to support the national reform agenda.